Administrasi Kurikulum - Azilla Fauza; Cindy Aulia; Alifah Syakira Najla (Universitas Serambi Mekkah, 2025)
The educational process in teaching and learning activities or in the classroom can run effectively, smoothly, conditionally, and interactively if education is carried out well when the curriculum becomes the main support in the teaching and learning process. The curriculum contains various constructive elements to ensure that learning runs optimally. Several curriculum experts argue that the heart of education lies in the curriculum. The quality of education results is determined by the curriculum, whether it is able to build critical awareness among students or not. One aspect that can improve the success of the curriculum is the empowerment of management or curriculum administration in the educational institution, in other words, the curriculum administration in that institution. This article uses a qualitative method with a library research approach, which involves examining relevant reading sources and using document studies from previous research results related to curriculum administration. Data collection is done by exploring books, scientific journals published on Google Scholar, digital libraries, and online libraries. The Law No. 20 of 2003 on the National Education System, Article 1, Paragraph (19), states that the curriculum is a set of plans and arrangements regarding the objectives, content, and teaching materials, as well as the methods used as guidelines for organizing learning activities to achieve specific educational goals. The curriculum is a set of learning experiences for students, with all the implementation guidelines systematically arranged and followed by the school in educating students. The process of curriculum administration includes planning, implementation, supervision, and evaluation.